Two Cases of Chloromethylisothiazolinone and Methylisothiazolinone-associated Toxic Lung Injury - Lee, Eun; Son, Seung Kook; Yoon, Jisun; Cho, Hyun-Ju; Yang, Song-I; Jung, Sungsu; Do, Kyung-Hyun; Cho, Young Ah; Lee, So-Yeon; Park, Dong-Uk; Hong, Soo-Jong (Journal of Korean medical science, 2018)
Previous animal studies have not conclusively determined the association between exposure to humidifier disinfectants (HDs) containing 5-chloro-2-methyl-4-isothiazolin-3-one (CMIT) and/or 2-methyl-4-isothiazolin-3-one (MIT) and development of HD-associated lung injuries. Nonetheless, patients exposed to HDs containing only CMIT and/or MIT showed clinically similar lung injuries to those exposed to HDs containing polyhexamethylene guanidine (PHMG) or oligo (2-[2-ethoxy]ethoxyethyl) guanidinium chloride (PGH). Here, we report twin sisters with lung injuries associated with exposure to CMIT/MIT-containing HDs. At 6 months of age, a younger twin sister presented with the 3-day history of cough, sputum, and respiratory difficulty. Chest radiography revealed multiple patchy consolidation and ground-glass opacities with pneumothorax and pneumomediastinum. Thoracostomy was performed due to pneumothorax at admission and she was discharged at 11 days of hospitalization. At 5 years of age, multiple tiny nodules and faint centrilobular ground-glass opacities were observed with the small pneumatocele. The elder sister visited a tertiary hospital due to dyspnea at 12 months of age. Chest radiography showed consolidation, pneumomediastinum, and pulmonary interstitial emphysema. There was no response to the administration of immunosuppressant drugs and antifibrotic agents. At 5 years of age, chest CT revealed ground-glass opacity and multiple tiny centrilobular ground-glass opacities nodules in both lungs with exercise intolerance.